The 823rd hit - Scaletta, Kurtis (Amulet Books, 2012)
These fun, illustrated early chapter books feature the adventures—and misadventures—of the Pine City Porcupines, a hapless baseball farm team, and their two batboys: Chad, an avid baseball fan with a huge baseball card collection, and Dylan, who doesn’t know a thing about the sport. The fictional series has a unique twist: Chad solves problems by using information from Topps cards of real figures from modern baseball history.